Quantification of postural control deficits in patients with recent concussion: an inertial-sensor based approach. Issue 11 (25th May 2017) - Doherty, Cailbhe; Caulfield, Brian; Ryan, John; Komaba, Yusuke; Inomata, Akihiro; Zhao, Liang
Abstract : Objective: To quantify postural control ability in a group with concussion compared with a 'healthy' control group. Design: Case-control study. Setting: University Biomechanics Laboratory. Participants: Fifteen concussion patients (4 females, 11 males) and a group of fifteen age- and sex- matched controls. Participants were excluded if they had any: lower extremity injury that may affect gait; history of cognitive deficiencies; history of ≥3 previous concussions; loss of consciousness following the concussion for >1 minute; a previously documented concussion in the previous year Independent variable: Group; Task (3 stance variants of the Balance Error Scoring System [BESS]) Outcome measures: Sway area as computed using a force-plate and sway volume as computed from an accelerometer placed on the sacrum during performance of the BESS. Main results: Concussed patients exhibited increased sway area (1500 mm 2 [95% CI: 900 to 2000 mm 2 ] vs 650 mm 2 [95% CI: 520 to 780 mm 2 ] p=0.02) and sway volume (9.5 m 3 s –6 [95%CI: 8 to 20 m 3 s –6 ] vs 2.80 m 3 s –6 [95% CI: 1.8 to 3.6 m 3 s –6 ]) in the bilateral stance position of the BESS. The sway volume metric also had excellent accuracy in identifying task 'errors' (tandem stance: 95% CI: 80–96%, p<0.001; unilateral stance: 95% CI: 85–95%, p<0.001). Conclusions: Individuals with concussion display increased postural sway during bilateral stance. The sway volume that was calculated from the accelerometer data not only differentiated a group with concussion from a healthy control group, but successfully identified when task errors had occurred. This may be of value in the development of a pitch-side assessment system for concussion. Competing interests: None.